Mapping Sea Surface Temperature and Its Correlation with The Acidity of Sea Water on the Coast of Kwanyar Madura Island - Siti Zainab; Novie Handajani; Hendrata Wibisana (Future Science)
Sea surface temperature is one parameter to determine the condition of the ecosystem of a waters, besides that there are other parameters, namely the acidity of sea water which is a number that indicates the degree of an ac id and base of the aquatic environment, where generally the coastal environment has an acidity value below 8 so that changes from this value will disrupt life as a whole for the coastal environment. The purpose of this study is to find a mathematical model of SST and pH that can describe the situation of the coastal area, where as a case study is the Kwanyar coast in Bangkalan district, Madura Island. The method developed here is the least square method to find the optimum mathematical model of these parameters, in addition to that by calculating the algorithm of several channels of visible wavelengths owned by Aqua Modis images which are 412 nm, 531 nm and 667 nm. The results obtained from this study are for the optimum wavelength of sea surface temperature is 667 nm while for pH is 531 nm. From the statistical analysis for the t-test carried out, the results showed no significant correlation between sea surface temperature with a pH value where both parameters showed a statistically low correlation value with an error rate of 5% and the existing Pearson correlation test equipment. The conclusion is that for the Kwanyar Bangkalan coastline the temperature is still in the normal threshold as well as the existing pH value, only these two parameters cannot be stated as a causal relationship, where the temperature rise will have an impact on pH changes and vice versa.